A Publish/Subscribe System Using Causal Broadcast over Dynamically Built Spanning Trees - Araujo, João Paulo de; Arantes, Luciana; Duarte, Elias P.; Rodrigues, Luiz A.; Sens, Pierre (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2017)
In this paper we present VCube-PS, a topic-based Publish/Subscribe system built on the top of a virtual hypercube-like topology. Membership information and published messages to subscribers (members) of a topic group are broadcast over dynamically built spanning trees rooted at the message's source. For a given topic, delivery of published messages respects causal order. Performance results of experiments conducted on the PeerSim simulator confirm the efficiency of VCube-PS in terms of scalability, latency, number, and size of messages when compared to a single rooted, not dynamically, tree built approach.